Fuel-constrained joint heat and power dynamic economic environmental dispatch - Basu, Mousumi; Jena, Chitralekha; Khan, Baseem; Ali, Ahmed; Bokoro, Pitshou (Frontiers in Energy Research, 2023)
The economical use of available fuel for producing electricity has been a very important challenge for power companies due to the continuously declining supply of fossil fuel. FCJHPDEED (Fuel Constrained Joint Heat and Power Dynamic Economic Environmental Dispatch) and JHPDEED (Joint Heat and Power Dynamic Economic Environmental Dispatch) with DSM (Demand Side Management) integrating solar PV plants, WTGs (wind turbine generators) and PHS (Pumped Hydro Storage) plant have been presented. Using the SPEA 2 (Strength Pareto Evolutionary Algorithm 2) and the NSGA-II (nondominated sorting genetic algorithm II), FCJHPDEED and JHPDEED have been solved. It is seen that the results obtainedwithout fuel constraints are more optimal than the results obtained with fuel constraints. Joint heat and power dynamic economic dispatch, cost obtained with fuel constraints is about 2.14% more than the cost obtained without fuel constraints and joint heat and power dynamic emission dispatch, emission obtained with fuel constraints is about 6.7% more than the emission obtained without fuel constraints.